Capacity Building Workshop on Genetic Resources for CGIAR Scientists and Partners from Near East and Neighbouring Countries, 17 - 20 September 2018, ICARDA, Beirut, Lebanon - CGIAR Genebank Platform (Bioversity International, 2019)
In September 2018, the CGIAR Genebank Platform Policy Module joined the International Center for Agricultural Research in Dry Areas (ICARDA) and the Association of Agricultural Research Institutions in the Near East and North Africa (AARINENA) to organize a capacity-building workshop on genetic resource policies for CGIAR scientists and partners from Near East and neighbouring countries. The workshop was held from 17 - 20 September 2018, hosted by ICARDA, Beirut, Lebanon. This event brought together 20 staff members from 6 CGIAR Centres (including genebank managers and technical staff, plant breeders, senior scientists, legal counselor and genetic resources policy specialists), 16 representatives of national agricultural research organizations in Afghanistan, Iraq, Jordan, Kuwait, Lebanon, Oman, Pakistan, Syrian Arab Republic and Yemen, and representatives of the Secretariats of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA), the Convention on Biological Diversity (CBD) and the coordination team of the Global Project on Access and Benefit Sharing of the United Nations Development Programme (UNDP). The workshop was designed to increase participants’ understanding of the CGIAR Centres’ obligations vis-à-vis international treaties and conventions dealing with access and benefit-sharing, and how these international instruments influence the day-to-day management of scientists, researchers and support staff involved in the management of plant germplasm collections and plant breeding prorgammes at national and international levels. The workshop included participatory analyses of practical case studies and hypothetical scenarios where the interface between the Nagoya Protocol on Access and Benefit Sharing and the ITPGRFA (Plant Treaty) can raise legal and procedural issues. It also addressed improving genebank operations and communications and as such, enhancing availability and accessibility of ex situ collections and promoting farmers’ rights.